The effects of nano-silica on early-age hydration reactions of nano Portland cement. (October 2022) - Dong, Peng; Allahverdi, Ali; Andrei, Carmen M.; Bassim, Nabil D.
Abstract: The hydration reactions of nano Portland cement (NPC) with and without nano-silica (NS) additives were realized and tracked for the first time in a liquid cell transmission electron microscope (LC-TEM), coupled with isothermal calorimetry and quantitative X-ray diffraction (QXRD). We revealed the different hydration mechanisms in NPC and PC in the presence of NS. The results showed that NS shortened the dissolution and induction periods of the hydration reaction significantly in normal PC systems. The fact that NS contributed less to hydration reactions in NPC systems resulted from the size effect. Nano cement with a much higher surface area and reactivity hydrated much faster to a high degree by itself. The LC-TEM observations found that NS was adsorbed on the surfaces of needle-like ettringite crystals accelerating their conversion into monosulfate, and thus achieving lower contents of ettringite in NPC with NS. Highlights: The differences of hydration kinetics of Portland cement in microscale and nanoscale are clarified. Ettringite formation and transformation is a dynamic process. The formation of a more stable hydration product, monosulfate, reduces the active surface of C–S–H for further precipitation. Nano-silica absorbed to needle-like ettringite crystals, accelerates the conversion of ettringite to monosulfate.